Infection by Syngamidae in seabirds along the Brazilian Coast: new occurrences of Cyathostoma - Alves, André Mota; Figueiredo, Larissa Mello; de Brito, Elaine Knupp; Vergara Parente, Jociery Einhardt; do Nascimento, Claudia Carvalho [UNESP]; Sarmento, Carlos Alberto Palmeira; de Medeiros, Iara Gama; Lima, Victor Fernando Santana; Borges, João Carlos Gomes (Springer Nature, 2025)
This study reports new occurrences of Syngamidae nematodes, specifically Cyathostoma (Cyathostoma) phenisci, in seabirds stranded along the northeastern coast of Brazil. Through systematic monitoring efforts of seabird strandings along the coast of Sergipe (northeastern Brazil), deceased specimens were subjected to post-mortem analyses. During necropsies, nematodes were identified in the tracheae of three specimens (Calonectris borealis, Puffinus puffinus, and Ardenna gravis), indicating respiratory infections. The parasites were collected and identified as C. phenisci. This represents the first record of this species in birds of the order Procellariiformes in Brazil. This study expands the known host range for this parasite and suggests a potential underreporting of respiratory infections caused by Syngamidae in seabirds. The findings underscore the importance of continuous monitoring of these populations and their implications for the health and conservation of migratory birds.
Keywords: Ardenna; Calonectris; Nematoda; Parasites; Puffinus; Seabirds